The Effect of Beeswax Concentration on Characteristics of Biodegradable Foam from Starch Waste Cassava Peel - Emmaria Eunike Rappitawati; Nanik Hendrawati (Jurnal Ilmiah Teknik Kimia, 2023)
Biodegradable Foam is used as an alternative to environmentally friendly food packaging or containers. Starch is the main ingredient in making biodegradable foam because it is cheap, easy to find, low density, and has high biodegradability. However, biodegradable foam from starch has a high water absorption ability, therefore the addition of beeswax is expected as a coating agent to reduce water absorption. This study aims to see the results of the addition of beeswax concentration and the length of time of immersion of the coating to the characteristics of biodegradable foam. This study used starch from cassava skin. The concentration of beeswax used was 5%, and 6% w/t by weight, while the coating time was varied from 1.5; 2, 2,5 ; 3 to 3.5 minutes. The application of beeswax on biodegradable foam produced the best results at a beeswax concentration of 6% with a time of 3 minutes, with a water absorption test result of 3.33%, a biodegradability test of 57.142% and a tensile strength test of 9.14 MPa.